Objectivity in the Shadows of Political Turmoil: A Comparative Content Analysis of News Framing in Post-Revolution Egypt’s Press - Elkamel, Sara Farag (AUC Knowledge Fountain, 2013)
This research study investigates the news frames that emerge in newspaper coverage of current affairs in the diverse post-revolution Egyptian mediascape. The study samples Al Ahram, Al Wafd, the Freedom and Justice Party paper, Al Masry Al Youm, and Al Shorouk, five major dailies that represent the three categories of ownership prevalent in Egyptian media – government owned, partisan, and independent papers. Using quantitative content analysis methodology with framing theory as a backdrop, this comparative research study aims to identify the dominant frames used across different outlets in the local press landscape to represent different political actors and issues in Egypt’s post-revolutionary political scene. The sampling period is the first nine months of the term of Egypt’s first-ever democratically elected president, Mohamed Morsi. The total sample yielded 290 articles. The results show that the five newspapers employed frames that mirrored their respective affiliations and ownership. Government-run Al Ahram and the Freedom and Justice Party paper employed frames that favored the ruling regime, Al Wafd took a decidedly anti-President Morsi tone, and independent papers Al Shorouk and Al Masry Al Youm exhibited more balanced coverage. The study's findings provide an important post-revolution baseline for Egyptian journalism that can be used to monitor the progression of news performance as the country’s transition to democracy unfolds.